Living theory the application of classical social theory to contemporary life - Hurst, Charles E. (Allyn and Bacon, 2000)
This book is provocative and current in the issues it addresses. Although the book presents substantial information on the core content of classical social theories, its focus is on the application of theoretical arguments to social distance and separation in the U.S. Hurst chose Marx, Durkheim, Simmel, and Weber as classical representatives. Readers will be interested in social theory if they can understand its relevance to what's happening in society today. This engaging new book does just that ""Living Theory"" analyzes major features of modern society from the classical theory point of view, and suggests how postmodern qualities might be accounted for by this theory. Chapters focus on specific issues such as the conflict between the rights of individuals and their obligations to society, the Internet's influence on transforming private lives into public information, gated communities and racial ghettos, political corruption, treating individuals as commodities in the world of beauty, entertainment and medicine, and the growing discrepancies in economic resources between individuals and groups. For anyone interested in classical social theory and social problems.